From Criminal to Rehabilitated Prison Reformer: Gradual Identity Transformation in Charles McGregor's Prison Autobiography "Up from the Walking Dead" - Katharina Matuschek (Current Objectives of Postgraduate American Studies)
This article examines how social roles are narratively constructed in Charles McGregor’s prison autobiography Up from the Walking Dead“ (1978) and investigates which significance the protagonist’s prison experiences have for this process. The construction of a criminal role which is reinforced by the prison experience is analyzed, and it is argued that the transformation process the protagonist undergoes is constructed as occurring despite the institution of prison.